Some Advanced Functionalities of Optical Amplifiers 2015
DOI: 10.5772/61664
|View full text |Cite
|
Sign up to set email alerts
|

Gallium Nitride-based Semiconductor Optical Amplifiers

Abstract: GaN-based material can potentially cover a wide spectral emission ranμe, and laser diodes emittinμ in the UV, violet, blue, μreen, and red wavelenμths have already been demonstrated and/or commercialized. GaN-based semiconductor optical ampliλiers SOAs have the ability to boost the output power oλ laser diodes and thus are candidates λor a broad variety oλ potential uses. Applications that utilize short wavelenμth, ultraλast pulses, includinμ microprocessinμ, orthoptics, and next-μeneration optical storaμe can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Nevertheless, in a recent work [13], it was shown that a small‐signal gain of 19 dB is achievable with a very compact optical amplifier with a 400 µm wavelength. Moreover, in [14] the basic characteristics of GaN‐based SOAs were reviewed, focusing on pulse amplification. GaN‐based SOAs can potentially cover a particularly wide spectral range, from the deep ultra violet to the infrared and can be employed in a variety of applications that utilise short wavelength, ultra‐fast pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in a recent work [13], it was shown that a small‐signal gain of 19 dB is achievable with a very compact optical amplifier with a 400 µm wavelength. Moreover, in [14] the basic characteristics of GaN‐based SOAs were reviewed, focusing on pulse amplification. GaN‐based SOAs can potentially cover a particularly wide spectral range, from the deep ultra violet to the infrared and can be employed in a variety of applications that utilise short wavelength, ultra‐fast pulses.…”
Section: Introductionmentioning
confidence: 99%